Pengaruh Kualitas Layanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan di Hotel Gading Beach Maumere - Anggun Raja Manu; Yoseph Darius P. Rangga; Nunsio H. Meylano (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study to (1) understand the overview of Service Quality and Customer Satisfaction in relation to Customer Loyalty at Gading Beach Hotel Maumere; and (2) analyze the influence of Service Quality and Customer Satisfaction on Customer Loyalty at Gading Beach Hotel Maumere, both partially and simultaneosly.The population in this study consisted of customers at Gading Beach Hotel Maumere. The Sample size was determined using Cochran’s formula, resulting in a total of 96 respondents. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted using F-test and t-test.The descriptive analysis results indicated that the Customer Loyalty variable was categorized as good, the Service Quality variable was categorized as fairly good, and the Customer Satisfaction variable was categorized as fairly good. The t-test results showed that, partially, the Service Quality variable had a significand influence on Customer Loyalty. Maeanwhile, the Customer Satisfaction variable, when considered individually, did not significantly affect Customer Loyalty. The F-test results demonstrated that both Service Quality and Customer Satisfaction variables had a significant effect on Customer Loyalty when considered simultaneosly. The coefficient of determination analysis showed that the relationship between the independet variables and customer loyalty was interpreted as low.